Fathers and sons in the Arab Middle East - Cohen-Mor, Dalya 1948- (Palgrave Macmillan, A Division of St. Martin's Press LLC, 2013)
Drawing on insights from psychology, sociology, anthropology, religion, history, and literature, this book examines early and contemporary writings of male authors from across the Arab world to explore the traditional and evolving nature of father-son relationships in Arab families